2019
DOI: 10.1186/s12881-019-0746-6
|View full text |Cite
|
Sign up to set email alerts
|

A possible founder mutation in FZD6 gene in a Turkish family with autosomal recessive nail dysplasia

Abstract: BackgroundAutosomal recessive nail dysplasia is characterized by thick and hard nails with a very slow growth on the hands and feet. Mutations in FZD6 gene were found to be associated with autosomal recessive nail dysplasia in 2011. Presently, only seven mutations have been reported in FZD6 gene; five mutations are clustered in the C-terminus, one is at the seventh transmembrane domain, and another is at the very beginning of third extracellular loop.MethodsWhole exome sequencing (WES) was applied to the index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…As a minority member of the family, FZD6 is a negative regulator of the typical Wnt/β-catenin signalling cascade. 29,30 It has been reported that FZD6 is upregulated in some cancer types, such as colorectal cancer, pancreatic cancer or esophageal cancer, and promotes the growth and metastasis of cancer cells, and it is also associated with low overall survival. 30 In a study by Cheng et al, 31 FZD6 as an inhibitor of the Wnt signalling pathway was extensively linked to miRNAs, and inhibition of FZD6 can reduce the tumourigenic behavior of GB in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a minority member of the family, FZD6 is a negative regulator of the typical Wnt/β-catenin signalling cascade. 29,30 It has been reported that FZD6 is upregulated in some cancer types, such as colorectal cancer, pancreatic cancer or esophageal cancer, and promotes the growth and metastasis of cancer cells, and it is also associated with low overall survival. 30 In a study by Cheng et al, 31 FZD6 as an inhibitor of the Wnt signalling pathway was extensively linked to miRNAs, and inhibition of FZD6 can reduce the tumourigenic behavior of GB in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…We studied one of these candidates, FZD6, which is a member of the “frizzled” gene family; this family encodes proteins with seven transmembrane domains and an N‐terminal extracellular domain encoded by a cysteine‐rich domain. As a minority member of the family, FZD6 is a negative regulator of the typical Wnt/β‐catenin signalling cascade 29,30 . It has been reported that FZD6 is upregulated in some cancer types, such as colorectal cancer, pancreatic cancer or esophageal cancer, and promotes the growth and metastasis of cancer cells, and it is also associated with low overall survival 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Directly, receptor 6 is a negative regulator of the Wnt/β-catenin signaling cascade, thereby inhibiting cell proliferation and apoptosis. Deletion in this gene was found to be associated with the development of autosomal recessive nail dysplasia [ 31 ]. FZD6 has also been implicated in the development of malignant esophageal carcinoma in humans [ 32 ].…”
Section: Discussionmentioning
confidence: 99%